Measuring The Gaps Between The Research And Statistical Skills And The Training Needs Of Graduate Students - Teong , Mee Mee (2010)
This study was initiated by the lack of research-based study to provide reliable and valid information regarding graduate students’ training needs in the area of research and statistics. The primary purpose of this study was to examine the graduate students’ state of preparedness in conducting and evaluating research literature, their knowledge base and their training needs in the area of research and statistics. The secondary purpose was to identify the graduate students’ demographic and situational variables that may explain or predict the overall training needs.